Farmer Types and Measuring Capacity for Climate Adaptation - Chiranjeevi, T.; Rout, Sanjit Kumar; Sreenivas, Y. (International Journal of Economic Plants, 2016)
Farmers in rainfed regions are going to be the hardest hit from the climate change. They need to adjust their livelihoods to be able to sustain themselves. A number of farmers may simply be not able to sustain or change their livelihoods because of the multiple constraints they face. It is necessary from the policy point of view to know the best and least prepared among these farmers. We find that a large number of SC, BC and women farmers in these regions have a very poor resource base as they lack access to irrigation, have poorer soils, lack in physical resources like farm equipment and financial resources like access to loans etc. Besides lacking in formal education they also have very little information about the climate change, its impacts and the possible methods of adaptation. Apart from the conventional types the other category is , farmers with low endowments on all capitals. These farmers are the most vulnerable with very limited options for adaptation. These are the marginal and small farmers from socially disadvantaged sections. Farming for these farmers is a gamble with rains. They invest small sums (though to them it could be their entire savings) and generally go for crops which worked well for others. They cannot spend much time on their own plots because they have to earn additional income from other sources.